EFFECTS OF GAMMA RAYS ON THE PHYSICAL STABILITY OF CARBOMERS AND CELLULOSE DERIVATIVES GEL BASES - Tonglairoum, Prasopchai; Ngawhirunpat, Tanasait; Opanasopit, Praneet; Panomsuk, Suwannee (Thai Bulletin of Pharmaceutical Sciences, 2017)
This study was designed to investigate the effects of gamma rays on the physical stability of gel bases. The influences of amounts of gamma rays (0, 16.5 and 25 kGrays), gelling agents and gel concentrations were assessed. Five gelling agents (Carbomer 934, Carbomer 940, methylcellulose (MC), hydroxyethylcellulose (HEC) and hydroxypropylcellulose (HPC)) were employed in this study. The physical stability of the gel bases, before and after freeze-thaw cycle, was evaluated from the physical appearance, viscosity and pH of the gel bases. The results revealed that the studied parameters of all gel bases changed after being exposed to the grammar ray. The higher the gamma rays used resulted in the lower viscosity of the gel bases. Gamma rays also had an effect on the viscosity of the gel bases after freeze-thaw cycle. Thus, the stability of the gel bases needs to be taken into account when using gamma rays as an alternative to sterilize or inhibit the microbial growth in gel bases.